Pengaruh Konsentrasi KOH yang Berbeda Terhadap Kualitas Alginat Rumput Laut Coklat Sargassum duplicatum J. G. Agardh - Anwar, Fauzi; Djunaedi, Ali; Santosa, Gunawan Widi (977-2407769)
Indonesia has plentiful resources and high biological diversity. One of them is brown seaweed Sargassum duplicatum which has potential as source for alginate. Alginate is often used in food and other industry, however extraction method is still becoming handycap to get high quality alginate. The objective of research was to know the effect of different concentration of soaking media KOH on quality of alginate. The method used was laboratory experiment. Design experiment applied was Completely Randomized Design (CRD) with three different concentrations of KOH, namely 0.3%, 0.5%, and 0.7%. Each treatment was repeated three times. The result showed that the highest yield was obtained at 0.3% KOH concentration at 33.63 ± 2.11%. The highest viscosity was obtained at 0.7% KOH concentration at 23.33 ± 2.08 cPs. The lowest water content was obtained at 0.7% KOH concentration at 14.71 ± 0.32%. The ashes content was obtained at 0.7% KOH concentration at 27.82 ± 0.88%.